Daya Proteksi Ekstrak Kulit Jeruk Purut (Citrus hystrix) Terhadap Nyamuk Demam Berdarah - Roy Nusa Rahagus; Joni Hendri (Loka Litbang Kesehatan Pangandaran, 2013)
The used of chemicals as mosquitos repellent may causing health problems. Extract of caffir lime (Citrus hystrix) as mosquitos repellent can be used as another option. The study aimed to analyze the protection capacity of C. hystrix against Aedes aegypti and Ae. albopictus. Experimental studies using completely randomized design was done. The obtained data were calculated using the protection capacity formula and analysed using t-test. The result indicated that protection capacity of Citrus hystrix extract for 6 hours on average gave 34.82% of protection against Ae. aegypti and 41.44% of Ae. albopictus. The caffir lime extract has been able to reject Ae. aegypti and Ae. albopictus. Although the thrust of the caffir lime is not as good as chemical products, but can be use as alternative mosquitoes repellent.